VD_FINDINFO Arrêt / 2020 / 758 vom 15. Dezember 2020 - VD Tribunal cantonal (2020)
IMPOTENCE MOYENNE, ALLOCATION POUR IMPOTENT, DÉBUT, DROIT À LA PRESTATION D'ASSURANCE | 48 al. 1 LAI, 48 al. 2 LAI, 48 LAI, 38 RAI